The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-70095-x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo rescue of recombinant very virulent IBDV using a RNA polymerase II driven system and primary chicken bursal cells

Abstract: infectious Bursal Disease Virus (iBDV), a member of the Birnaviridae family, causes an immunosuppressive disease in young chickens. Although several reverse genetics systems are available for IBDV, the isolation of most field-derived strains, such as very virulent IBDV (vvIBDV) and their subsequent rescue, has remained challenging due to the lack of replication of those viruses in vitro. Such rescue required either the inoculation of animals, embryonated eggs, or the introduction of mutations in the capsid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…Compared with the embryo’s CAM approach, this method requires higher skills on the part of the operator. Cubas-Gaona et al also rescued vvIBDV by transfecting into the DF-1 cells and then transferring the cell culture suspension to the primary chicken bursa cell for virus propagation [ 66 ]. However, primary bursa cells are cumbersome to make and not easy to culture.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the embryo’s CAM approach, this method requires higher skills on the part of the operator. Cubas-Gaona et al also rescued vvIBDV by transfecting into the DF-1 cells and then transferring the cell culture suspension to the primary chicken bursa cell for virus propagation [ 66 ]. However, primary bursa cells are cumbersome to make and not easy to culture.…”
Section: Discussionmentioning
confidence: 99%
“…The rescue of recombinant viruses rCu-1-p0 and rvv-p0 has been described recently (Cubas-Gaona et al, 2020). Briefly, DF-1 cells were transfected with recombinant expression vectors prACu-1 and prBCu-1 for rCu-1-p0 recovery or prAvv and prBvv for rvv-p0 recovery.…”
Section: Cell and Virusesmentioning
confidence: 99%
“…In the present study, two strains of IBDV produced from cloned DNA in a reverse genetics system (Cubas-Gaona et al, 2020) were used: one based on a non-passaged (p0), cellculture adapted, attenuated, vaccine-related and classical strain (rCu-1-p0), and a second one based on a non-passaged, noncell-culture adapted and very virulent strain (rvv-p0). rCu-1-p0 was serially passaged in DF-1 cells, chicken bursal cells (hereafter referred as chicken B cells), and chickens while rvv-p0 was exclusively passaged using chicken B cells to address four questions: (i) whether serial passaging of a homogeneous rvv-p0 virus population would select mutations previously observed upon wild-type heterogeneous vvIBDV adaptation to avian and mammalian cell cultures, (ii) whether serial passaging of homogeneous rCu-1-p0 virus population would select mutations associated to a reversion toward virulence of some heterogeneous live-attenuated vaccines, (iii) whether serial passaging in the presence of the adenosine analog 7-deaza-2 -C-methyladenosine (7DMA) would generate resistant mutants in one or both homogeneous virus populations, and (iv) whether potential resistant mutants would show an attenuated phenotype in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Neutralization assays are typically conducted with cell-culture adapted viruses that usually contain mutations in the HVR, and it is challenging for neutralizing antibodies to be characterized against field-strains with wild-type HVR sequences. Adapting IBDV field strains to replicate in immortalized adherent cell-culture is associated with mutations at amino acid positions 253, 279, 284 and 330 in the HVR, which are known to change antigenicity and virulence (1214, 26, 34). However, we demonstrated that there was no change in the residues at positions 253, 284 and 330 in our recombinant viruses, although strains Del-E and M04/09 had an N279H mutation following DT40 passage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and others demonstrated that field strains of IBDV can replicate within primary chicken bursal cells and the immortalised chicken B-cell line DT40 (19, 2125). Moreover, primary chicken bursal cells were used to rescue a molecular clone of a field strain of IBDV for the first time in 2020 (26), thus enabling the ability to study how mutations in the IBDV HVR contribute to antigenicity and immune escape in field strains.…”
Section: Introductionmentioning
confidence: 99%